Laminate and method for producing same
The laminated structure with specific particle size ratios and alloy formation addresses interface resistance issues, achieving high thermal conductivity and low thermal resistance in thermal conductive materials for LSIs.
Patent Information
- Application Number
- CN202380041297.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-08
- Filing Date
- 2023-05-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-05-25
AI Technical Summary
Existing thermal conductive materials used in LSIs face challenges with high contact resistance at interfaces, leading to reduced thermal conductivity and increased thermal resistance.
A laminated structure comprising a substrate with a first heat-conductive layer containing curing components, curing agents, first heat-conductive particles, and low-melting-point metal particles, and a second heat-conductive layer with similar components but different particle sizes, ensuring particle contact and alloy formation for improved thermal conductivity.
The laminated structure achieves high thermal conductivity and low thermal resistance by increasing contact area and forming a network of low-melting-point metal particles, enhancing thermal conductivity and reliability.
Smart Images

Figure CN119212868A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate and a method for producing the laminate. Background Art
[0002] In LSIs and the like in various electronic devices, if the LSI itself is exposed to high temperatures for a long time due to the heat generated by the components used, there is a concern that malfunction or failure may occur. Therefore, in order to prevent the temperature of LSIs and the like from rising, thermal conductive materials are widely used. The thermal conductive materials can prevent the temperature of the device from rising by diffusing or conducting the heat generated by the components to a heat dissipation component for dissipating the heat to the outside of the system such as the atmosphere.
[0003] If metal or ceramic is used as such a heat conducting material, it is difficult to reduce weight, has poor processability, or has low flexibility. Therefore, various heat conducting materials using polymer materials formed of resin, rubber, etc. as a base material have been proposed.
[0004] For example, a thermally conductive adhesive has been proposed, which includes a thermosetting adhesive containing a curing component and a curing agent for the curing component, and a metal filler dispersed in the thermosetting adhesive, the metal filler including silver powder and solder powder, the solder powder exhibiting a melting temperature lower than the heat curing treatment temperature of the thermally conductive adhesive and reacting with the silver powder under the heat curing treatment conditions of the thermosetting adhesive to generate a high melting point solder alloy exhibiting a melting point higher than the melting temperature of the solder powder, the curing agent being a curing agent having flux activity for the metal filler, the curing component being a glycidyl ether type epoxy resin, and the curing agent being a monoanhydride of a tricarboxylic acid (for example, refer to Patent Document 1).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 5796242 Summary of the invention
[0008] Problems to be solved by the invention
[0009] However, in the prior art described in Patent Document 1, when a heat conductive layer formed of a heat conductive adhesive is formed between a copper substrate and a silicon substrate, the contact resistance at the interface with silicon increases, thereby reducing the thermal conductivity.
[0010] The present invention aims to solve the above-mentioned problems and achieve the following objectives: That is, the present invention aims to provide a laminate and a method for producing the laminate that can achieve high thermal conductivity and low thermal resistance.
[0011] Methods for solving problems
[0012] The method for solving the above-mentioned problem is as follows.
[0013] <1> A laminated body, characterized in that it has:
[0014] Base material;
[0015] On the substrate, a first heat-conducting layer comprising a curing component, a curing agent for curing the curing component, first heat-conducting particles, and low-melting-point metal particles; and
[0016] On the first heat conductive layer, a second heat conductive layer including a curing component, a curing agent for curing the curing component, second heat conductive particles and low melting point metal particles is provided.
[0017] A portion of the first heat-conductive particles included in the first heat-conductive layer is in contact with a portion of the second heat-conductive particles included in the second heat-conductive layer, and a volume average particle size of the first heat-conductive particles is smaller than a volume average particle size of the second heat-conductive particles.
[0018] The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.
[0019] <2> The laminate according to <1>, wherein a ratio (A:B) of a volume average particle size A of the first heat conductive particles to a volume average particle size B of the second heat conductive particles is 1:2 to 1:50.
[0020] <3> The laminate according to <1> or <2>, wherein the first thermally conductive particles have a volume average particle size of 0.3 μm to 30 μm.
[0021] <4> The laminated body according to any one of <1> to <3>, wherein the second heat conductive particles have a volume average particle size of 1 μm to 100 μm.
[0022] <5> The laminated body according to any one of <1> to <4>, wherein the first heat-conductive particles and the second heat-conductive particles are at least any one of copper particles, silver-coated particles, and silver particles.
[0023] <6> The laminate according to any one of <1> to <5>, wherein the low-melting-point metal particles include Sn and at least one selected from Bi, Ag, Cu, and In.
[0024] <7> The laminated body according to any one of <1> to <6>, wherein the curing agent has flux activity with respect to the first heat conductive particles and the second heat conductive particles.
[0025] <8> The laminate according to any one of <1> to <7>, wherein the curing component is at least one of an oxirane ring compound and an oxetane compound.
[0026] <9> The laminated body according to any one of <1> to <8>, further comprising a third heat conductive layer between the first heat conductive layer and the second heat conductive layer.
[0027] <10> The laminate according to <9>, wherein the third heat conduction layer is a copper foil.
[0028] <11> The laminate according to any one of <1> to <10>, further comprising an opposing substrate on the second heat conductive layer that opposes the substrate.
[0029] The opposing substrate includes at least one selected from the group consisting of copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.
[0030] <12> A method for producing a laminate, characterized in that it comprises the following steps:
[0031] a first heat conductive layer forming step of forming a first heat conductive layer containing a curing component, a curing agent for curing the curing component, first heat conductive particles and low melting point metal particles on the substrate; and
[0032] a second heat conductive layer forming step of forming a second heat conductive layer including a curing component, a curing agent for curing the curing component, second heat conductive particles and low melting point metal particles on the first heat conductive layer;
[0033] The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.
[0034] Effects of the Invention
[0035] According to the present invention, the above-mentioned various problems of the related art can be solved, the above-mentioned objects can be achieved, and a laminated body and a method for producing the laminated body that can realize high thermal conductivity and low thermal resistance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a schematic diagram showing an example of the laminated body according to the first embodiment.
[0037] Figure 2 It is a schematic diagram showing an example of a laminated body according to the second embodiment.
[0038] Figure 3 This is a schematic cross-sectional view showing an example of a heat dissipation structure used in the present invention. DETAILED DESCRIPTION
[0039] (Laminated body)
[0040] The laminated body of the present invention comprises a substrate, a first heat conductive layer, and a second heat conductive layer, and preferably comprises a third heat conductive layer and an opposing substrate, and further comprises other members as required.
[0041] In the present invention, the first heat conductive layer and the second heat conductive layer are sequentially provided on the substrate, a part of the first heat conductive particles are in contact with a part of the second heat conductive particles, and the volume average particle size of the first heat conductive particles is smaller than the volume average particle size of the second heat conductive particles. Therefore, even if the substrate is formed of at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel and ceramics and has poor solder wettability, the thermal conductivity can be greatly improved as the contact area increases.
[0042] <Base material>
[0043] The shape, structure, size, material, etc. of the substrate are not particularly limited and can be appropriately selected depending on the purpose.
[0044] Examples of the shape of the substrate include a plate shape, a sheet shape, etc. Examples of the structure of the substrate include a single layer structure, a laminated structure, etc. The size of the substrate can be appropriately selected depending on the intended use, etc.
[0045] The material of the substrate is a material that is not easily wetted by solder, and includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel and ceramics. Examples of the ceramics include aluminum nitride, silicon carbide, aluminum oxide, gallium nitride, etc. Examples of the molding resin include epoxy resin, silicone resin, urethane resin, acrylic resin, etc.
[0046] The average thickness of the substrate is not particularly limited and can be appropriately selected depending on the intended purpose.
[0047] The substrate may be the heat generating element (electronic component) itself in the heat dissipating structure.
[0048] <1st heat transfer layer>
[0049] The first heat conductive layer is formed on the substrate, preferably in contact with the substrate. The first heat conductive layer contains a curing component, a curing agent for curing the curing component, first heat conductive particles, and low melting point metal particles, and further contains other components as needed.
[0050] -Curing ingredients-
[0051] As the curing component, it is preferred to use at least one of an oxirane ring compound and an oxetane compound.
[0052] --Oxirane ring compounds--
[0053] The oxirane ring compound is a compound having an oxirane ring, and examples thereof include epoxy resins.
[0054] As the above-mentioned epoxy resin, there is no particular restriction, and it can be appropriately selected according to the purpose, and for example, glycidyl ether type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A type epoxy resin, trisphenol type epoxy resin, tetraphenol type epoxy resin, phenol-xylylene type epoxy resin, naphthol-xylylene type epoxy resin, phenol-naphthol type epoxy resin, phenol-dicyclopentadiene type epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, etc. can be mentioned. They can be used alone or in combination of two or more.
[0055] --Oxetane compounds--
[0056] The oxetane compound is a compound having an oxetane group, and may be an aliphatic compound, an alicyclic compound, or an aromatic compound.
[0057] The oxetane compound may be a monofunctional oxetane compound having only one oxetane group, or may be a polyfunctional oxetane compound having two or more oxetane groups.
[0058] The oxetane compound is not particularly limited and can be appropriately selected according to the purpose. For example, 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, 1,4-bis(3-ethyl-3-oxetanylmethyl)ether, -3-oxetanylmethoxy)butane, 1,6-bis(3-ethyl-3-oxetanylmethoxy)hexane, 3-ethyl-3-(phenoxy)methyloxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, xylylenebisoxetane, 4,4′-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), etc. These may be used alone or in combination of two or more.
[0059] As the oxetane compound, a commercially available product can be used, and examples of the commercially available product include “ARONE OXETANE (registered trademark)” series sold by Toagosei Co., Ltd. and “ETERNACOLL (registered trademark)” series sold by Ube Industries, Ltd.
[0060] Among the above-mentioned oxirane ring compounds and oxetane compounds, preferred are glycidyl ether epoxy resins, phenol novolac epoxy resins, cresol novolac epoxy resins, phenol-dicyclopentadiene epoxy resins, bisphenol A epoxy resins, aliphatic epoxy resins, and 4,4′-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP).
[0061] The content of the curing component is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5 mass % to 60 mass % based on the total amount of the first heat conductive layer.
[0062] -Curing agent-
[0063] As the above-mentioned curing agent, it is a curing agent corresponding to the above-mentioned curing component, for example, anhydride curing agents, aliphatic amine curing agents, aromatic amine curing agents, phenol curing agents, thiol curing agents and other polyaddition curing agents, imidazoles and other catalyst curing agents, etc. can be mentioned. They can be used alone or in combination of two or more. Among these, anhydride curing agents are preferred.
[0064] The above-mentioned acid anhydride curing agent is preferred because it does not generate gas during thermal curing when the curing component is an epoxy resin, and can achieve a long storage period when mixed with the epoxy resin. In addition, it can achieve a good balance between the electrical properties, chemical properties and mechanical properties of the obtained cured product.
[0065] Examples of the acid anhydride curing agent include cyclohexane-1,2-dicarboxylic anhydride and tricarboxylic acid monoanhydride. Examples of the tricarboxylic acid monoanhydride include cyclohexane-1,2,4-tricarboxylic acid-1,2-anhydride.
[0066] The curing agent has flux activity, which is preferred from the perspective of improving the wettability of the molten low-melting-point metal particles relative to the thermally conductive particles. As a method for the curing agent to exhibit flux activity, for example, a method of introducing a protonic acid group such as a carboxyl group, a sulfonyl group, or a phosphate group into the curing agent using a known method can be cited. Among these, from the perspective of reactivity with an epoxy resin or an oxetane compound as a curing component, it is preferred to introduce a carboxyl group, and for example, organic acids containing carboxyl groups such as glutaric acid and succinic acid can be cited. In addition, it can be a compound modified by glutaric anhydride or succinic anhydride or a metal salt of an organic acid such as silver glutarate.
[0067] The content of the curing agent is not particularly limited and can be appropriately selected depending on the intended purpose, but is preferably 0.1 mass % to 30 mass % based on the total amount of the first heat conductive layer.
[0068] The molar equivalent basis equivalence ratio (C / D) of the curing component C to the curing agent D varies depending on the types of curing components and curing agents used and cannot be generally specified, but is preferably 0.5 to 3, more preferably 0.5 to 2, and even more preferably 0.7 to 1.5.
[0069] When the equivalent ratio (C / D) is 0.5 or more and 3 or less, there is an advantage that the low melting point metal particles are sufficiently melted and can form a network when the thermal conductive composition is thermally cured.
[0070] -First thermally conductive particle-
[0071] The first heat-conductive particles are preferably at least any one of copper particles, silver-coated particles, and silver particles.
[0072] Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles.
[0073] The shape of the first heat conductive particles is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include spherical, flat, granular, and needle-like shapes.
[0074] The volume average particle size of the first thermally conductive particles is preferably 0.3 μm to 30 μm, and more preferably 0.5 μm to 10 μm. If the volume average particle size of the thermally conductive particles is 0.3 μm to 30 μm, the volume ratio of the first thermally conductive particles to the low melting point metal particles can be increased, and high thermal conductivity and low thermal resistance can be achieved. The volume average particle size can be measured, for example, by a laser diffraction, scattered particle size distribution measuring device (product name: Microtrac MT3300EXII).
[0075] -Low melting point metal particles-
[0076] As the low melting point metal particles, solder particles specified in JIS Z3282-1999 are preferably used.
[0077] As the above-mentioned solder particles, for example, Sn-Pb solder particles, Pb-Sn-Sb solder particles, Sn-Sb solder particles, Sn-Pb-Bi solder particles, Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Cu solder particles, Sn-Pb-Cu solder particles, Sn-In solder particles, Sn-Ag solder particles, Sn-Pb-Ag solder particles, Pb-Ag solder particles, Sn-Ag-Cu solder particles, etc. can be cited. They can be used alone or in combination of two or more. Among these, preferably, a solder particle containing Sn and at least one selected from Bi, Ag, Cu and In is used, and more preferably, Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Ag-Cu solder particles, and Sn-In solder particles are used.
[0078] The shape of the low melting point metal particles is not particularly limited and can be appropriately selected depending on the intended purpose. Examples of the shape include spherical, flat, granular, and needle-like particles.
[0079] The melting point of the low-melting-point metal particles is preferably 100°C to 250°C, and more preferably 120°C to 200°C.
[0080] The melting point of the low-melting-point metal particles is lower than the heat curing treatment temperature of the first thermally conductive composition. This is preferred from the perspective that the low-melting-point metal particles melt in the cured product of the first thermally conductive composition and form a network (continuous phase of metal) through the first thermally conductive particles, thereby achieving high thermal conductivity and low thermal resistance.
[0081] The low melting point metal particles react with the thermally conductive particles under the heat curing conditions of the first thermally conductive composition to form an alloy having a higher melting point than the low melting point metal particles, thereby preventing melting at high temperatures and improving reliability. In addition, the heat resistance of the cured product of the first thermally conductive composition is improved.
[0082] The thermal curing treatment of the first thermally conductive composition is performed, for example, at a temperature of 150° C. to 200° C. for 30 minutes to 2 hours.
[0083] The volume average particle size of the low melting point metal particles is preferably 10 μm or less, and more preferably 1 μm or more and 5 μm or less. If the volume average particle size of the low melting point metal particles is 10 μm or less, the volume ratio of the low melting point metal particles to the thermally conductive particles can be reduced, and high thermal conductivity and low thermal resistance of the first thermally conductive layer can be achieved. The volume average particle size of the low melting point metal particles can be measured in the same manner as the volume average particle size of the first thermally conductive particles.
[0084] The volume average particle size of the first thermally conductive particles is larger than the volume average particle size of the low melting point metal particles, and the volume average particle size ratio (A / B) of the thermally conductive particles A to the low melting point metal particles B is preferably 2 or more, more preferably 3 or more, and further preferably 5 or more. The upper limit of the volume average particle size ratio (A / B) is preferably 20 or less, and more preferably 10 or less.
[0085] By using low-melting-point metal particles having a smaller volume average particle size than the first heat-conductive particles, the heat-conductive particles become the main component in the first heat-conductive composition, and the low-melting-point metal particles between the first heat-conductive particles are melted by heating and alloyed with the first heat-conductive particles to form a network, thereby achieving high thermal conductivity and low thermal resistance.
[0086] The volume ratio (A / B) of the first heat conductive particles A to the low melting point metal particles B in the first heat conductive layer is preferably 1 or more, more preferably 1.5 or more, and even more preferably 2 or more. The upper limit of the volume ratio (A / B) is preferably 5 or less, more preferably 4 or less, and even more preferably 3 or less.
[0087] If the volume ratio (A / B) is greater than 1, the volume ratio of the thermally conductive particles having a larger volume average particle size than the low melting point metal particles increases, thereby suppressing the flow of the molten low melting point metal particles. In addition, the low melting point metal particles are not easily separated even at an interface that is not easily wetted (for example, silicon), thereby suppressing the influence of the material of the interface and improving the selectivity of the interface material.
[0088] -polymer-
[0089] The first heat conductive layer preferably contains a polymer in order to impart flexibility and the like.
[0090] The polymer is not particularly limited and can be appropriately selected according to the purpose. Examples thereof include polymers having at least one structure selected from a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, a polyamide structure, and a polycarbonate structure in the molecule.
[0091] The content of the polymer is preferably 1 mass % to 50 mass % based on the total amount of the first heat conductive layer, more preferably 1 mass % to 30 mass %, and even more preferably 1 mass % to 10 mass %.
[0092] -Other ingredients-
[0093] The first thermally conductive layer may contain other components as long as the effects of the present invention are not impaired. The other components are not particularly limited and can be appropriately selected according to the purpose, and examples thereof include thermally conductive particles other than metals (e.g., aluminum nitride, aluminum oxide, carbon fibers, etc.), additives (e.g., antioxidants, ultraviolet absorbers, curing accelerators, silane coupling agents, leveling agents, flame retardants, etc.), and the like.
[0094] The first heat conductive composition can be prepared by uniformly mixing the curing component, the curing agent, the first heat conductive particles, the low melting point particles, the polymer, and other components as required by a conventional method.
[0095] The average thickness of the first heat conductive layer is not particularly limited and can be appropriately selected depending on the intended purpose, but is preferably 1 μm to 100 μm, and more preferably 5 μm to 50 μm.
[0096] <Second heat transfer layer>
[0097] The second heat conductive layer contains a curing component, a curing agent for curing the curing component, second heat conductive particles, and low melting point metal particles, and further contains other components as necessary.
[0098] - Second thermally conductive particles -
[0099] As the second heat-conductive particles, at least any one of copper particles, silver-coated particles, and silver particles is preferred.
[0100] Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles.
[0101] The shape of the second heat-conductive particles is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include spherical, flat, granular, and needle-like shapes.
[0102] It is necessary that a portion of the first heat-conductive particles included in the first heat-conductive layer is in contact with a portion of the second heat-conductive particles included in the second heat-conductive layer, and the volume average particle size of the first heat-conductive particles is smaller than the volume average particle size of the second heat-conductive particles. If the volume average particle size of the first heat-conductive particles is larger than the volume average particle size of the second heat-conductive particles, the thermal conductivity of the stacked body may be reduced.
[0103] The ratio of the volume average particle size A of the first heat-conductive particles to the volume average particle size B of the second heat-conductive particles (A:B) is preferably 1:2 to 1:50, and more preferably 1:10 to 1:40.
[0104] The volume average particle size of the second heat-conductive particles is preferably 1 μm to 100 μm, more preferably 10 μm to 70 μm, and even more preferably 10 μm to 50 μm. If the volume average particle size of the second heat-conductive particles is 1 μm to 100 μm, high thermal conductivity and low thermal resistance can be achieved. The volume average particle size of the second heat-conductive particles can be measured in the same manner as the volume average particle size of the first heat-conductive particles.
[0105] The curing component, curing agent, low melting point metal particles, polymer and other components in the second heat conductive layer are the same as those in the first heat conductive layer, and thus their details are omitted.
[0106] The average thickness of the second heat conductive layer is not particularly limited and can be appropriately selected depending on the intended purpose, but is preferably 20 μm to 300 μm, and more preferably 50 μm to 200 μm.
[0107] <Third heat transfer layer>
[0108] The third heat conductive layer is formed between the first heat conductive layer and the second heat conductive layer. The third heat conductive layer may be a single layer or may be a plurality of layers of two or more layers.
[0109] The third heat-conducting layer is preferably a copper foil from the viewpoint of thermal conductivity.
[0110] The average thickness of the third heat conductive layer is not particularly limited and can be appropriately selected depending on the intended purpose, but is preferably 5 μm to 200 μm, and more preferably 10 μm to 100 μm.
[0111] <Opposing substrate>
[0112] The opposing substrate is disposed to face the substrate, and its shape, structure, size, material, etc. are not particularly limited and can be appropriately selected depending on the purpose.
[0113] Examples of the shape of the opposing substrate include a plate shape, a sheet shape, etc. Examples of the structure of the opposing substrate include a single layer structure, a laminated structure, etc. The size of the opposing substrate can be appropriately selected according to the intended use, etc.
[0114] The material of the opposing substrate is a material that is easily wetted by solder, and includes at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.
[0115] The average thickness of the opposing substrate is not particularly limited and can be appropriately selected depending on the intended purpose.
[0116] The opposing substrate may be the heat dissipation module itself in the heat dissipation structure.
[0117] <Other components>
[0118] The other member is not particularly limited and can be appropriately selected depending on the purpose. For example, a protective layer etc. are mentioned.
[0119] (Method for producing laminated body)
[0120] The method for producing a laminated body of the present invention includes a first heat conducting layer forming step and a second heat conducting layer forming step, and further includes other steps as necessary.
[0121] <First heat conduction layer forming step>
[0122] The first heat conductive layer forming step is a step of forming a first heat conductive layer containing a curing component, a curing agent for curing the curing component, first heat conductive particles, and low melting point metal particles on the substrate.
[0123] The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.
[0124] The curing component, curing agent, first heat conductive particles, and low melting point metal particles are the same as those included in the first heat conductive layer, and thus description thereof is omitted.
[0125] Examples of the method for forming the first thermally conductive layer include (1) applying a first thermally conductive composition containing a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles to a substrate and curing the composition, and (2) forming a cured product layer containing a cured product of the first thermally conductive composition containing a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles on a support having a release layer, and transferring the cured product layer to the substrate. In (2), when the cured product layer is transferred to the substrate, the support is peeled off.
[0126] Examples of the method for applying the first thermally conductive composition to the substrate in (1) include inkjet coating, blade coating, gravure coating, gravure offset coating, rod coating, roll coating, knife coating, air knife coating, comma coating, U-comma coating, AKKU coating, smooth coating, micro gravure coating, reverse roll coating, 4-roll coating, 5-roll coating, dip coating, curtain coating, slide coating, and die coating.
[0127] <Second heat conduction layer forming step>
[0128] The second heat conductive layer forming step is a step of forming a second heat conductive layer including a curing component, a curing agent for curing the curing component, second heat conductive particles, and low melting point metal particles on the first heat conductive layer.
[0129] The curing component, the curing agent, the second heat-conductive particles, and the low-melting-point metal particles are the same as those included in the second heat-conductive layer, and thus description thereof is omitted.
[0130] Examples of the method for forming the second thermally conductive layer include (1) applying a second thermally conductive composition containing a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles to the first thermally conductive layer and curing the composition, and (2) forming a cured product layer containing a cured product of the second thermally conductive composition containing a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles on a support having a release layer, and transferring the cured product layer to the first thermally conductive layer. In the above (2), the support is peeled off when the cured product layer is transferred to the first thermally conductive layer.
[0131] Examples of the method for applying the second thermally conductive composition to the first thermally conductive layer in (1) include inkjet coating, blade coating, gravure coating, gravure offset coating, rod coating, roll coating, knife coating, air knife coating, comma coating, U-comma coating, AKKU coating, smooth coating, micro gravure coating, reverse roll coating, 4-roll coating, 5-roll coating, dip coating, curtain coating, slide coating, and die coating.
[0132] <Other Process>
[0133] The other steps are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include a third heat conduction layer forming step.
[0134] Here, about the embodiment of the laminated body of the present invention, it is described in detail with reference to the accompanying drawings. In addition, in each accompanying drawing, the same component is attached with the same symbol, and repeated description is sometimes omitted. In addition, the number, position, shape, etc. of the following constituent members are not limited to this embodiment, and can become a preferred number, position, shape, etc. on the basis of implementing the present invention.
[0135] <First embodiment>
[0136] Figure 1 1 is a schematic diagram showing an example of a laminated body according to the first embodiment. Figure 1The laminate 10 has a first heat conductive layer 12 containing first heat conductive particles 15 on a substrate 11 , a second heat conductive layer 13 containing second heat conductive particles 16 on the first heat conductive layer 12 , and an opposing substrate 14 on the second heat conductive layer 13 .
[0137] Part of the first heat conductive particles 15 included in the first heat conductive layer 12 is in contact with part of the second heat conductive particles 16 included in the second heat conductive layer 13 , and the volume average particle size of the first heat conductive particles 15 is smaller than that of the second heat conductive particles 16 .
[0138] <Second embodiment>
[0139] Figure 2 2 is a schematic diagram showing an example of a laminated body according to the second embodiment. Figure 2 In the laminated body 20, a first heat-conductive layer 12 containing first heat-conductive particles 15 is provided on a substrate 11, a third heat-conductive layer 17 as a copper foil is provided on the first heat-conductive layer 12, a second heat-conductive layer 13 containing second heat-conductive particles 16 is provided on the third heat-conductive layer 17, and an opposing substrate 14 is provided on the second heat-conductive layer 13.
[0140] Part of the first heat conductive particles 15 included in the first heat conductive layer 12 and part of the second heat conductive particles 16 included in the second heat conductive layer 13 are in contact with each other through the third heat conductive layer 17 . The volume average particle size of the first heat conductive particles 15 is smaller than that of the second heat conductive particles 16 .
[0141] For example, the laminate of the present invention can be suitably used to form a power LED module or a power IC module by filling the tiny gap between a heat source such as an LSI and a heat sink, thereby connecting a heat dissipating substrate mounted with a thermal interface material (TIM) that allows heat to flow smoothly between the two, an LED chip or an IC chip, and a heat sink.
[0142] Here, as the power LED module, there are a module of a wire bonding mounting type and a module of a flip chip mounting type, and as the power IC module, there is a module of a wire bonding mounting type.
[0143] The heat dissipation structure used in the present invention is composed of a heat generating body, the laminated body of the present invention, and a heat dissipation member.
[0144] The heat generating element is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include electronic components such as a CPU (Central Processing Unit), an MPU (Micro Processing Unit), and a GPU (Graphics Processing Unit).
[0145] The heat dissipating member is not particularly limited as long as it is a structure that dissipates heat generated by an electronic component (heat generating element), and can be appropriately selected depending on the purpose. Examples thereof include heat dissipating modules, heat sinks, temperature equalizing plates, and heat pipes.
[0146] The heat dissipation module is a member for efficiently conducting the heat of the electronic component to other components. The material of the heat dissipation module is not particularly limited and can be appropriately selected according to the purpose, for example, copper, aluminum, etc. The heat dissipation module is usually in a flat plate shape.
[0147] The heat sink is a member for releasing the heat of the electronic component into the air. There is no particular limitation on the material of the heat sink, and it can be appropriately selected according to the purpose, for example, copper, aluminum, etc. The heat sink, for example, has a plurality of fins. The heat sink, for example, has a base, and a plurality of fins extending in a non-parallel direction (for example, an orthogonal direction) relative to one surface of the base.
[0148] Generally speaking, the heat dissipation module and the heat dissipation fin are solid structures without any space inside.
[0149] The temperature equalizing plate is a hollow structure. A volatile liquid is sealed in the inner space of the hollow structure. Examples of the temperature equalizing plate include a temperature equalizing plate having a hollow structure in the heat dissipation module and a hollow structure in the plate shape such as the heat sink.
[0150] The heat pipe is a hollow structure in a cylindrical, substantially cylindrical or flat cylindrical shape, and a volatile liquid is sealed in the inner space of the hollow structure.
[0151] here, Figure 3 FIG. 1 is a schematic cross-sectional view showing an example of a semiconductor device as a heat dissipation structure. The laminate 7 of the present invention dissipates the heat generated by the electronic components 3 such as semiconductor components. Figure 3 As shown, the main surface 2a fixed to the heat dissipation module 2 and facing the electronic component 3 is sandwiched between the electronic component 3 and the heat dissipation module 2. In addition, the thermally conductive sheet 1 is sandwiched between the heat dissipation module 2 and the heat dissipation sheet 5.
[0152] The heat dissipation module 2 is formed in a square plate shape, for example, and has a main surface 2a facing the electronic component 3, and a side wall 2b erected along the outer periphery of the main surface 2a. The heat dissipation module 2 is provided with a heat conductive sheet 1 on the main surface 2a surrounded by the side wall 2b, and a heat sink 5 is provided on the other surface 2c on the opposite side of the main surface 2a through the heat conductive sheet 1. The higher the thermal conductivity of the heat dissipation module 2, the lower the thermal resistance, and the heat of the electronic component 3 such as the semiconductor component is efficiently absorbed. For example, it can be formed using copper or aluminum with good thermal conductivity.
[0153] Electronic component 3 is, for example, a semiconductor component such as BGA, and is mounted on wiring board 6. In heat dissipation module 2, the front end surface of side wall 2b is mounted on wiring board 6, thereby surrounding electronic component 3 at a predetermined distance via side wall 2b.
[0154] Furthermore, by providing the laminated body 7 of the present invention on the main surface 2 a of the heat dissipation module 2 , heat generated by the electronic component 3 is absorbed, and a heat dissipation member is formed that dissipates the heat through the heat sink 5 .
[0155] Example
[0156] Hereinafter, examples of the present invention will be described, but the present invention is not limited to these examples.
[0157] (Examples 1 to 5, Comparative Examples 1 to 3 and Reference Example 1)
[0158] <Preparation of thermally conductive composition>
[0159] The compositions and contents listed in Tables 1 to 3 were uniformly mixed using a stirring device (Rentaro Automatic Revolution Mixer, manufactured by THINKY Co., Ltd.) to prepare the first thermally conductive composition and the second thermally conductive composition. The contents of the components in Tables 1 to 3 are parts by mass.
[0160] <Formation of laminated body>
[0161] Next, in Examples 1 to 5 and Comparative Example 3, according to the descriptions in Tables 1 to 3, the first thermally conductive composition was applied to a substrate (silicon) of 30 mm×30 mm×2 mm, and then the second thermally conductive composition was applied to the first thermally conductive layer. A counter substrate (copper) of 30 mm×30 mm×2 mm was stacked on the second thermally conductive composition, and the composition was heated at 150° C. for 60 minutes to be cured, thereby forming a laminate having a first thermally conductive layer with an average thickness of 10 μm and a second thermally conductive layer with an average thickness of 70 μm.
[0162] In Example 2, a copper foil having an average thickness of 30 μm was used as the third heat conducting layer.
[0163] In Reference Example 1 and Comparative Example 1, except that the first thermally conductive composition was not used, a laminate was formed in the same manner as in Examples 1 to 5 and Comparative Example 3. In Reference Example 1, a substrate (copper) of 30 mm × 30 mm × 2 mm was used instead of a substrate (silicon) of 30 mm × 30 mm × 2 mm.
[0164] In Comparative Example 2, a laminate was formed in the same manner as in Examples 1 to 5 and Comparative Example 3, except that the second thermally conductive composition was not used.
[0165] Next, thermal resistance and thermal conductivity of each of the obtained laminated bodies were evaluated as follows. The results are shown in Tables 1 to 3.
[0166] <Thermal impedance>
[0167] The thermal resistance (°C·cm) of each obtained laminate was measured by the method according to ASTM-D5470. 2 / W). The thermal resistance of the cured product was calculated by subtracting the thermal resistance of the substrate and the opposing substrate from the result. The thermal impedance (Kmm) was calculated from the thermal resistance and the area of the cured product. 2 / W).
[0168] <Thermal conductivity>
[0169] The thermal resistance (°C·cm) of each obtained laminate was measured by the method according to ASTM-D5470. 2 / W). The thermal resistance of the cured product was calculated by subtracting the thermal resistance of the substrate and the opposing substrate from the result, and the thermal conductivity (W / m·K) was determined from the thermal resistance and the thickness of the cured product. The thermal conductivity was evaluated according to the following criteria.
[0170]
Evaluation criteria
[0171] ◎: Thermal conductivity 15W / m·K or more
[0172] ○: Thermal conductivity is 10W / m·K or more and less than 15W / m·K
[0173] ×: Thermal conductivity is less than 10W / m·K
[0174]
Table 1
[0175]
[0176]
Table 2
[0177]
[0178]
Table 3
[0179]
[0180] The details of each component in Tables 1 to 3 are as follows.
[0181] -Curing ingredients-
[0182] *OXBP: 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl manufactured by Ube Industries, Ltd.
[0183] -Curing agent-
[0184] *Polycarboxylic acid, synthetic product of Dexerials Co., Ltd.
[0185] -Low melting point metal particles (solder particles)-
[0186] *Sn 42 Bi 58 : Made by Mitsui Mining & Smelting Co., Ltd., volume average particle size Dv: 4 μm, melting point 139°C
[0187] -First thermally conductive particle-
[0188] * First thermally conductive particles 1: Ag particles, manufactured by DOWA Electronics Co., Ltd., volume average particle size Dv: 1 μm
[0189] * First thermally conductive particles 2: Ag-coated Cu particles, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., volume average particle size Dv: 5 μm
[0190] * First thermally conductive particles 3: Ag-coated Cu particles, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., volume average particle size Dv: 40 μm
[0191] - Second thermally conductive particles -
[0192] * Second thermally conductive particles 1: Ag-coated Cu particles, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., volume average particle size Dv: 40 μm
[0193] * Second thermally conductive particles 2: Cu particles, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., volume average particle size Dv: 40 μm
[0194] * Second thermally conductive particles 3: Ag particles, manufactured by DOWA Electronics Co., Ltd., volume average particle size Dv: 1 μm
[0195] -polymer-
[0196] *M1276: Made by Arkema Co., Ltd., polyamide compound
[0197] Industrial Availability
[0198] The laminate of the present invention can achieve high thermal conductivity and low thermal resistance as a thermal interface material (TIM), and is therefore suitable for use in various electrical device peripherals such as CPUs, MPUs, power transistors, LEDs, laser diodes, etc., where the efficiency and life of component operation are adversely affected by temperature.
[0199] This application claims priority based on Japanese Patent Application No. 202-93004 filed with the Japan Patent Office on June 8, 2022, and cites all the contents described in the above application.
[0200] Explanation of symbols
[0201] 1 Thermal conductive sheet
[0202] 2 Cooling module
[0203] 2a Main side
[0204] 3. Heat generating element (electronic components)
[0205] 3a Top
[0206] 5 Heat sink
[0207] 6 Wiring board
[0208] 7 Laminated body
[0209] 10 Laminated body
[0210] 11. Substrate
[0211] 12. 1st thermal conductive layer
[0212] 13. Second thermal conductive layer
[0213] 14 Opposing substrate
[0214] 15 No. 1 thermally conductive particles
[0215] 16. Second thermally conductive particle
[0216] 17 Third thermal conductive layer
[0217] 20 Laminated
Claims
1. A laminate, characterized in that: have: Base material; On the substrate, a first heat conductive layer including a curing component, a curing agent for curing the curing component, first heat conductive particles, and low melting point metal particles; and On the first heat conductive layer, a second heat conductive layer including a curing component, a curing agent for curing the curing component, second heat conductive particles and low melting point metal particles is provided. A portion of first heat-conductive particles included in the first heat-conductive layer is in contact with a portion of second heat-conductive particles included in the second heat-conductive layer, and a volume average particle size of the first heat-conductive particles is smaller than a volume average particle size of the second heat-conductive particles. The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, a molding resin, stainless steel, and ceramics.
2. The laminate according to claim 1, A ratio (A:B) of a volume average particle size A of the first heat-conductive particles to a volume average particle size B of the second heat-conductive particles is 1:2 to 1:
50.
3. The laminate according to claim 1 or 2, The first thermally conductive particles have a volume average particle size of 0.3 μm or more and 30 μm or less.
4. The laminate according to claim 1 or 2, The second heat-conductive particles have a volume average particle size of 1 μm or more and 100 μm or less.
5. The laminate according to claim 1 or 2, The first heat-conductive particles and the second heat-conductive particles are at least any one of copper particles, silver-coated particles, and silver particles.
6. The laminate according to claim 1 or 2, The low-melting-point metal particles include Sn and at least one selected from Bi, Ag, Cu, and In.
7. The laminate according to claim 1 or 2, The curing agent has flux activity with respect to the first heat-conductive particles and the second heat-conductive particles.
8. The laminate according to claim 1 or 2, The curing component is at least one of an oxirane ring compound and an oxetane compound.
9. The laminate according to claim 1 or 2, A third heat conducting layer is provided between the first heat conducting layer and the second heat conducting layer.
10. The laminate according to claim 9, The third heat conducting layer is copper foil.
11. The laminate according to claim 1 or 2, A counter substrate facing the substrate is provided on the second heat conducting layer. The opposing substrate includes at least one selected from the group consisting of copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.
12. A method for producing a laminate, characterized in that: The process includes the following steps: a first heat conductive layer forming step of forming a first heat conductive layer including a curing component, a curing agent for curing the curing component, first heat conductive particles, and low melting point metal particles on the substrate; as well as a second heat conductive layer forming step of forming a second heat conductive layer including a curing component, a curing agent for curing the curing component, second heat conductive particles and low melting point metal particles on the first heat conductive layer; The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, a molding resin, stainless steel, and ceramics.
Citation Information
Patent Citations
Thermal interface material based on composite thermal-conduction network of low-melting-point metals and thermal-conduction particles, and preparation method of thermal interface material
CN108912683A
Thermal radiation sheet having multilayer structure
KR101379437B1
High thermal conductivity composite solder
TW201522604A
Thermally conductive adhesive
US20130279118A1
Composite thermal interface materials, thermal interface components, and methods for making the same
US20190092994A1
